1-(3-methyl-3-phenylcyclobutyl)-2-(piperidin-1-yl) ethanone oxime - Dincer, M; Özdemir, N; Cukurovali, A; Yilmaz, I; Büyükgüngör, O (Int Union Crystallography, 2006)
The asymmetric unit of the title compound, C18H26N2O, contains two molecules. In both molecules, the oxime group has an E configuration and the piperidine ring adopts a chair conformation. Intramolecular C-H (...) O and intermolecular O-H (...) N hydrogen bonds are observed in the crystal structure.
Keywords: Oxiconazole; Crystal